Gauging Reactive Metabolites in Drug-Induced Toxicity - R. Eno, Marsha; D. Cameron, Michael (Current Medicinal Chemistry, 2015)
Over the past decades, it has become abundantly clear that enzymes evolved to detoxify and eliminate foreign chemicals from the body, occasionally generate highly reactive metabolites which have toxicological implications. To decrease the probability of late clinical failure or market withdrawal, there has been an increased prioritization on understanding key metabolic processes that might cause drug interactions or toxicities. Significant advances have been made in the detection of reactive metabolites and in understanding the structure activity relationship. It is now widely accepted that compounds with certain functional groups such as anilines, quinones, hydrazines, thiophenes, furans, acylpropionic acids, and alkynes have a much greater associated risk towards formation of reactive metabolites than compounds that do not contain such “structural alerts”. Detection of reactive metabolites is usually done with in vitro assays, which have become more sensitive with advances in mass spectrometry. As an increasingly large number of compounds that form reactive metabolites have been identified, much of the focus has shifted from detection to evaluation of toxicological implication. While there is a disproportionate number of compounds metabolized to reactive metabolites that are associated with drug-induced hepatotoxicity and serious skin toxicities such as toxic endothelial necrolysis and Steven’s Johnson syndrome, attempts to predict toxicity based on in vitro testing have been discouraging. In this review we attempt to summarize the experimental options available to evaluate reactive metabolites.
Keywords: hepatotoxicity